ESSKA instructional course lecture book : Amsterdam 2014 - Becker, Roland; Kerkhoffs, Gino M.M.J; Espregueira Mendes, Joao; Dijk, C. Niek; Stefano Zaffagnini (Springer Berlin Heidelberg, 2014)
This book provides an update on a wide variety of hot topics in the field of knee surgery, sports trauma, and arthroscopy, covering the latest developments in basic science and clinical and surgical methods. It comprises the Instructional Course Lectures delivered at the 16th ESSKA Congress, which was held in Amsterdam during May 2014 and brought together the world's leading orthopaedic and sports physicians. The contributions are all written by European and international experts in their field. Each lecture has a practical focus and provides an up-to-date synthesis of core knowledge on the subject in question with the aid of high-quality illustrations. Take home messages and key recommendations are highlighted. This book will be of value to practitioners and researchers alike.